Russian-Turkish Relations In The Balance Of The Ukrainian Crisis Challenges Of Involvement And Balance - شكوحي, إياد; عفيف حيدر ,; شادي شهيلة, (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Both Russia and Turkey were able to build advanced bilateral relations، reinforced by understandings that surround contentious issues، and nullify their effects and impact on economic cooperation between the two countries to preserve their very important economic gains to restore their position on the international scene، even though Russia is strongly motivated and qualified more than Turkey to break international balances and formulate balances new، enabling it to regain its active and influential presence in the international system. Ukraine is one of the most important areas in which Russia seeks to break the international balances that crystallized after the dissolution of the Soviet Union، as it allowed the United States of America to threaten Russian national security through it. The Russian special military operation in Ukraine came to miss the opportunity for the West in its endeavor to threaten the Russian depth. But this process has put Turkey in front of severe challenges، as it is keen to adopt a position that goes in line with Western policies towards Russia، but without disturbing Russia، and raising its fears of Turkey's possible return، always to the American and NATO prodding.